Draft Five Year Plan 1978-83 General Areas Vol. II Agriculture and Allied Services Including Co-operation Government of Assam - Planning Commission (Planning Commission, 1978)
The soils of the plain area are generally alluvial. The new alluvial soils which cover larger part of the Brahmaputra valley are sandy or loamy soils of neutral reaction having moderate levels of available phosphorous and potash. The older alluvial soils the south of the valley and upper Assam are some what acidic and poorer in phosphorous. The mountain valley alluvial soils of Cachar are more acidic than the other two groups.
Planning and Development Department, Government of Assam
Planning and Development Department, Government of Assam